A Legal Semantic Anthropological Reading of Kataba: Constructing the Qur’anic Evidentiary Order of Debt - Mohammad Luthfil Anshori (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2026)
Qur’an 2:282 is often read as a legal instruction to record deferred debt, leaving the social and evidentiary significance of kataba underexplored. This article examines how kataba moves beyond graphic writing to shape an evidentiary order for debt transactions. The study uses qualitative library research based on mawḍūʿī-nuzūlī theory, supported by lexical-semantic analysis, comparative exegesis, and legal anthropology as a limited conceptual lens. Its primary sources include classical Arabic lexicons and the commentaries of al-Ṭabarī, al-Qurṭubī, al-Rāzī, and Ibn ʿĀshūr. The findings show that the semantic associations of k-t-b with gathering, binding, prescribing, and obligating become relevant only through the structure of the verse. Although exegetes disagree over whether fa-uktubūhu indicates obligation or strong recommendation, they share a concern with protecting rights, strengthening proof, and preventing disputes. The verse establishes an evidentiary order through the debtor’s dictation, the impartial work of the kātib bi al-ʿadl, testimony, and protection for scribes and witnesses. This structure articulates documentary consciousness as the normative expectation that financial rights and obligations should acquire a readable and verifiable form capable of establishing responsibility.  QS. al-Baqarah 282 sering dipahami sebagai dasar hukum pencatatan utang bertempo, tetapi makna sosial dan pembuktian dari kataba belum banyak dikaji secara mendalam. Artikel ini menelaah bagaimana kataba tidak hanya menunjuk tindakan menulis, melainkan membentuk tata bukti dalam transaksi utang. Dengan menggunakan teori mawḍūʿī-nuzūlī sebagai kerangka utama, analisis dilakukan melalui penelitian kepustakaan kualitatif yang memadukan kajian leksikal-semantik, perbandingan tafsir, dan antropologi hukum sebagai lensa konseptual terbatas. Sumber utama yang digunakan meliputi leksikon Arab klasik serta tafsir al-Ṭabarī, al-Qurṭubī, al-Rāzī, dan Ibn ʿĀshūr. Temuan artikel menunjukkan bahwa makna akar k-t-b yang berkaitan dengan menghimpun, mengikat, menetapkan, dan mewajibkan memperoleh relevansinya melalui struktur ayat. Meskipun para mufasir berbeda pendapat mengenai status hukum fa-uktubūhu, mereka sama-sama menempatkan penulisan sebagai sarana menjaga hak, menguatkan bukti, dan mencegah sengketa. Ayat ini membangun tata bukti melalui pendiktean debitur, kātib bi al-ʿadl, persaksian, dan perlindungan terhadap penulis serta saksi. Struktur tersebut membentuk kesadaran dokumentatif bahwa hak dan kewajiban finansial perlu memiliki bentuk yang dapat dibaca, diverifikasi, dan dipertanggungjawabkan.